Ekoteologi dalam Al-Qur’an : Studi Tematik atas Ayat-ayat Tentang Krisis Lingkungan dan Tanggung Jawab Manusia - Luthviyah Romziana; Zakiyatus Surur (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research stems from the awareness that the modern environmental crisis is not only ecological but also spiritual and theological. Nature, which should be a sign of Allah's greatness, has been exploited due to an anthropocentric view that places humans at the center of reality. The Qur'an contains fundamental ideas about the relationship between God, humans, and nature based on tauhid (monotheism), balance, and moral responsibility. This research explores the concept of ecotheology in the Qur'an through maudhu'i (thematic) exegesis using a theological and ethical approach. The steps include collecting verses about nature and the environment, analyzing contexts based on classical interpretations such as al-Ṭabarī and al-Qurṭubī, as well as modern interpretations like al-Mishbah and Fī Ẓilāl al-Qur'ān. Data are analyzed qualitatively to find the theological construction of ecology. The hypothetical results indicate that the Qur'an presents an ecotheological paradigm that positions nature as kauniyyah verses (cosmic signs), not objects of exploitation. Humans as caliphs (vicegerents) have a spiritual responsibility to maintain the balance of Allah's creation. Qur'anic ecotheology rests on four pillars: ecological tauhid, responsible caliphate, ecological trusteeship, and mīzān (balance). These four pillars form an Islamic environmental theological framework for solving the contemporary ecological crisis